Penggunaan E-wallet di Kalangan Mahasiswa - Hizbul Hadi Nawawi (Emik, 2020)
Internet users are growing rapidly from time to time throughout the world, including Indonesia. As a result, consumer needs in terms of making payments have changed towards non-cash payments, namely e-wallets, which have become a huge potential in the e-commerce market. The preference for e-wallet transactions is increasing compared to using cash on hand. Most of its users are millennials, including students. This study examines knowledge related to the use of e-wallets and the reasons behind its use. The study involve ten college students, consisting of nine female students, and a male student whose age varies between 19 and 23 years. They come from various universities. Using qualitative approach, this study use in-depth interview as the primary data collection technique and secondary data obtained from relevant website. This research shows that e-wallet is not only understood as a place to store money electronically, but also as a digital payment. In Indonesia there are various e-wallet products. Among others OVO, Gopay, and DANA are the most popular ones. There are three aspects related to the students’ knowledge about e-wallet: source of information, features, and its use. Advertisements from social media, television, and transportation applications are the main sources of information about e-wallets. E-wallet offered various features, such as topping up, paying bills and pulses, and transferring and withdrawing from e-wallets to bank partners. E-wallet is used for a variety of purpose, such as to pay online transportation, to buy food/drinks, to pay bills, etc. There are three basic reasons why students use e-wallet as a payment method, namely because of the promos offered, convenience in transactions, and ease to operate. To attract people to use e-wallets, service providers must work with various merchants, whose promos are increasingly attracting users to use e-wallet for payment. In using e-wallets, students not only feel comfortable, but also convenience in payment because it can be done anywhere as long as the user is connected to the internet. Keywords : Millenial generation, students, e-wallet, internet, cashless, and digital payment.